Facilitating patient portal engagement: a channel expansion and behavior change wheel perspective - Cao, Weidan; Cao, Xiaohui (Frontiers in Communication, 2024)
Given the low patient portal adoption rates, the contradictory findings on the relationship between patient-provider communication and patient portal use, and the unclear mechanism of why doctor-patient communication might facilitate portal use as indicated in some existing studies, patient portal engagement warrants further examination. Guided by the behavior change wheel framework and the channel expansion theory, this study examined the facilitators of patient portal engagement and tested the relationship between the facilitators (e.g., social opportunity and psychological capability) through analyzing the HINTS national survey data (N = 1251). We found that patient portal access (a physical opportunity) and physician advocacy (a social opportunity) were two significant predictors of portal engagement while educational attainment was not. We did not find any direct correlation between patient-centered communication (PCC) and patient portal engagement, but instead, found a significant indirect relationship between the two. To the best of our knowledge, this is the first study to employ the behavior change wheel and channel expansion theory to explain patient portal engagement.Theoretically, our study extended the behavior change theory by further explaining the relationship between the key components (e.g., capability, opportunity) of behavior change.Practical strategies to increase patient portal engagement were proposed.